High hydrostatic pressure applied to ready-to-eat meat products: focus on Listeria monocytogenes inactivation - Teixeira, Paula (2015)
Several non-thermal technologies, particularly high pressure processing,have showngood potential in effective food preservation. The main interest in these technologies results from their potential to inactivate pathogenic microorganisms in foods, without substantially altering their nutritional value and organoleptic properties. This review focuses on the application of high pressure processing as an emerging technology and its application in ready-to-eat meat products regarding Listeria monocytogenes inactivation. Updated findings on the benefits and drawbacks for industrial applications are also reviewed.